Radiation protection for Radiotracers in oil industry - Osamah Saud Salman (Journal of Madenat Alelem University College, 2022)
Radioactive tracers are radiological technologies that are used in many fields, especially the medical fields and the oil and gas industry, as they reduce the cost of drilling and oil production and workers are exposed to ionizing radiation, which requires the existence of a radiation protection program for the purpose of protecting workers from the risks of radiation exposure and because radioactive materials are classified among the hazardous materials, it is necessary to establish work procedures for the purpose of protecting workers in normal situations and even in case of radiological emergency. This research discussed a scenario of radiation exposure to one of the workers, as it was assumed that the radiation dose is 50 cm away from 235 mSvh-1, which is greater than the internationally permitted and recommended limits. The amount of 10mSvh-1 which requires preventive measures to be taken to reduce the effect of external exposure to reduce the radiation dose by the radiation protection official.